The Effectiveness of Comparative Foot Soaks using Red Ginger Decoction and Lemongrass Decoction in Reducing Blood Pressure in Pregnant Women with Hypertension - Ratu Balgis Babay; Risnawati Risnawati; Juda Julia Kristiarini (Journal La Medihealtico, 2025)
Hypertension in pregnancy is a major cause of maternal and fetal morbidity and mortality, with serious complications such as preeclampsia, eclampsia, stroke, and even death. Data in Kotamobagu City in 2025 showed that 59 of 295 pregnant women (13.9%) experienced hypertension. Non-pharmacological efforts, such as herbal-based complementary therapies, are still rarely used due to lack of knowledge among the public and health workers. The research method used a quasi-experimental pretest-posttest with a control group design. A sample of 30 respondents was divided into three groups: red ginger (n=10), lemongrass (n=10), and control (n=10). The research instruments included an aneroid sphygmomanometer, a stopwatch, a water thermometer, an observation sheet, and an intervention SOP. Data analysis was performed using the Wilcoxon Signed Rank Test and Kruskal-Wallis with a significance level of 0.05. The results showed that red ginger foot baths reduced systolic blood pressure by an average of 22 mmHg and diastolic blood pressure by 14 mmHg (p=0.007; p=0.004), while lemongrass reduced systolic blood pressure by 27 mmHg and diastolic blood pressure by 11 mmHg (p=0.004; p=0.008). The control group did not show a significant decrease (p>0.05). The Kruskal-Wallis test showed a significant difference between the groups (p=0.000 systolic; p=0.032 diastolic), with lemongrass being more effective on systolic blood pressure, while red ginger was more dominant on diastolic blood pressure. In conclusion, red ginger and lemongrass foot baths are effective as a safe complementary therapy for hypertensive pregnant women, and have the potential to be a supporting intervention for antenatal care.